2002
DOI: 10.1074/jbc.m100567200
|View full text |Cite
|
Sign up to set email alerts
|

Basic Calcium Phosphate Crystals Induce Matrix Metalloproteinase-1 through the Ras/Mitogen-activated Protein Kinase/c-Fos/AP-1/Metalloproteinase 1 Pathway

Abstract: Synovial fluid basic calcium phosphate (BCP) crystals are common in osteoarthritis and are associated with severe degenerative arthropathy. Besides stimulating synovial fibroblast-like cells to proliferate, BCP crystals are a potent inducer of human matrix metalloproteinases (hMMPs), which can speed up the articular joint tissue degeneration of osteoarthritis patients. Here, we report that transfections with hMMP1 luciferase reporter plasmids in fibroblast-like synoviocytes revealed that the induction of hMMP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…In addition, a polyoma virus enhancer 3 (PEA-3) binding site at the proximal promoter region is also involved in the induction of human MMP1 (16). Interestingly, AP-1 has been shown to interact with PEA-3 (17) and SMAD proteins (17,18), and such an interaction potentiates the activity of AP-1.…”
mentioning
confidence: 99%
“…In addition, a polyoma virus enhancer 3 (PEA-3) binding site at the proximal promoter region is also involved in the induction of human MMP1 (16). Interestingly, AP-1 has been shown to interact with PEA-3 (17) and SMAD proteins (17,18), and such an interaction potentiates the activity of AP-1.…”
mentioning
confidence: 99%
“…Such inhibitors also reduce severity of collagen-induced arthritis (an animal model of RA) by suppressing Ras and IKK-mediated activation of NF-B (53). Previously observed suppression of bone destruction by dominant negative Ras may be partly due to inhibition of proteases such as ADAMTS-4 and MMPs (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that Ginkgolon-24, an extract of Ginkgo Biloba L., suppressed the production of MMP-1 induced by oxLDL and 4-HNE in hCSMCs, suggesting that this inhibitory activity is also involved in the therapeutic effects of the extract on cardiovascular disorders 28) and intimal hyperplasia in ballooninjured abdominal aorta in an animal model 29) . With regard to the mechanisms responsible for the production of MMP-1, the induction of MMP-1 gene expression was mediated by ERK1/2 in canine fibroblast-like synoviocytes 34) . The activation of ERK1/2 was mediated by the activation of receptors for growth factors such as PDGFR-in SMCs 36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of hCSMCs with oxLDL (50 g/mL) for 24h induced an increase in MMP-1 protein in the culture medium, as estimated by immunoblotting, as shown in The induction of MMP-1 gene expression is suggested to be mediated by ERK1/2 in canine fibroblastlike synoviocytes stimulated with basic calcium phosphate crystals 34) . We also reported that oxLDL and 4-HNE induces the activation of ERK1/2, inhibition of which by PD98059, an inhibitor of mitogen-activated protein kinase/ERK kinase, resulted in the suppression of MMP-1 production in hCSMCs 15) , suggesting the involvement of ERK1/2 in the production of MMP-1.…”
Section: Effects Of Ginkgolon-24 On the Production Of Mmp-1 And The Amentioning
confidence: 99%